Measuring the Role of Female Auditor Behavior: Evidence in Indonesia - Saifudin Saifudin; Indira Januarti; Jake M. Laguador (JASF: Journal of Accounting and Strategic Finance, 2025)
Purpose: This research aims to further examine the factors that cause the underrepresentation of female auditors in Indonesian public accounting firms in their professional behavior. Method: The data were collected through the implementation of experimental methods in between subjects with 2x2x2 factorial design, which involved a total of 104 participants, including partners, managers, senior staff, and junior staff, whose data were collected directly at the IAPI training in Semarang City. Data processing was then carried out using ANOVA and regression approaches. Findings: The results show that female and male auditors exhibit equivalent levels of professional skepticism. This indicates that the professionalization and standardization of auditing create convergence in professional competencies, regardless of gender differences. However, female auditors exhibit slightly higher levels of audit communication behavior than male auditors. This is manifested in a more comprehensive disclosure of audit information and a preference for participatory communication. Female auditors exhibit higher levels of organizational culture behavior, as evidenced by a stronger awareness of the importance of organizational ethical values and a supportive work environment. Implications: These findings suggest that public accounting firms should eliminate gender-based biases in professional recruitment and promotion, as the convergence of professional skepticism indicates that core auditing competencies are gender-neutral. Firms are encouraged to implement gender-diversity policies that move beyond representation, focusing instead on integrating the unique behavioral strengths into specialized auditor training and leadership development programs. Novelty/Value: This study employs experimental design to integrate moral sensitivity theory and explain complex gender differences in auditing, providing practical implications for gender diversity policies and auditor training.